REKONSTRUKSI PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF HUMANIS-RELIGIUS - Iskandar Mirza; Dedi Sukandar; Eli Herdiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Islamic Religious Education (IRE) faces increasingly complex challenges due to social transformation, the advancement of digital technology, and the dynamics of modern society. To date, IRE learning has tended to emphasize cognitive and normative aspects, thereby limiting its capacity to fully develop the human dimensions of learners. This article aims to analyze the urgency of reconstructing Islamic Religious Education through a humanistic-religious approach as an effort to create a learning process that is more relevant to the needs of contemporary students. This study employs a library research method by examining scholarly literature, SINTA-indexed journal articles, and other relevant academic sources. The findings reveal that the humanistic-religious paradigm in Islamic Religious Education positions learners as educational subjects endowed with innate potential (fitrah), freedom, dignity, and spiritual responsibility. The reconstruction of IRE can be achieved through the strengthening of dialogical learning, the integration of humanistic and religious values, the transformation of teachers’ roles from knowledge transmitters to facilitators and mentors, and the development of assessment systems that evaluate not only cognitive achievement but also attitudes and behavior. The humanistic-religious approach contributes to the formation of learners who are religious, tolerant, critical, and socially responsible. Consequently, Islamic Religious Education is expected not merely to produce individuals who understand Islamic teachings textually, but also those who are capable of implementing Islamic values in their daily lives.